Ex vivo culture of cells derived from circulating tumour cell xenograft to support small cell lung cancer research and experimental therapeutics. (13th December 2018) - Lallo, Alice; Gulati, Sakshi; Schenk, Maximilian W; Khandelwal, Garima; Berglund, Ulrika Warpman; Pateras, Ioannis S; Chester, Christopher P E; Pham, Therese M; Kalderen, Christina; Frese, Kristopher K; Gorgoulis, Vassilis G; Miller, Crispin; et al.
Abstract : Background and Purpose: Small cell lung cancer (SCLC) is an aggressive disease with median survival of <2 years. Tumour biopsies for research are scarce, especially from extensive‐stage patients, with repeat sampling at disease progression rarely performed. We overcame this limitation for relevant preclinical models by developing SCLC circulating tumour cell derived explants (CDX), which mimic the donor tumour pathology and chemotherapy response. To facilitate compound screening and identification of clinically relevant biomarkers, we developed short‐term ex vivo cultures of CDX tumour cells. Experimental Approach: CDX tumours were disaggregated, and the human tumour cells derived were cultured for a maximum of 5 weeks. Phenotypic, transcriptomic and pharmacological characterization of these cells was performed. Key Results: CDX cultures maintained a neuroendocrine phenotype, and most changes in the expression of protein‐coding genes observed in cultures, for up to 4 weeks, were reversible when the cells were re‐implanted in vivo . Moreover, the CDX cultures exhibited a similar sensitivity to chemotherapy compared to the corresponding CDX tumour in vivo and were able to predict in vivo responses to therapeutic candidates. Conclusions and Implications: Short‐term cultures of CDX provide a tractable platform to screen new treatments, identify predictive and pharmacodynamic biomarkers and investigate mechanisms of resistance to better understand the progression of this recalcitrant tumour.